2009
DOI: 10.1590/s1519-69842009000300022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence between Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum (Siluriformes: Pimelodidae) in the Paraná River Basin

Abstract: Pseudoplatystoma corruscans (Spix and Agassiz, 1829) and Pseudoplatystoma reticulatum (Eingenmann and Eigenmann, 1889) are large migratory catfishes of high biological importance and great commercial value in South America. Because fertile crossbreeds can be artificially produced in hatcheries, a high genetic proximity between these two Pimelodidae species is conceivable. Possible escape of crossbred specimens from pisciculture stations is a serious environmental concern. Despite their importance, knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 14 publications
1
21
0
6
Order By: Relevance
“…Large migratory fishes like Salminus brasiliensis (dourado), Pseudoplatystoma corruscans (pintado), Brycon orbignyanus (piracanjuva), Pinirampus pirinampu (barbado), Hemisorubim platyrhynchos (jurupoca), Prochilodus lineatus (corimba), Piaractus mesopotamicus (pacú) and Zungaro jahu (jaú) are common in both ecoregions. Population genetics studies of some of these species above and below the Itaipu Dam suggest they are not isolated populations (Bignoto et al, 2009). These findings suggest that in years of very high discharge, individuals of large migratory species were able to cross the barrier of the Sete Quedas Falls in both directions.…”
Section: Final Consideration and Implications For Biodiversity Consermentioning
confidence: 91%
“…Large migratory fishes like Salminus brasiliensis (dourado), Pseudoplatystoma corruscans (pintado), Brycon orbignyanus (piracanjuva), Pinirampus pirinampu (barbado), Hemisorubim platyrhynchos (jurupoca), Prochilodus lineatus (corimba), Piaractus mesopotamicus (pacú) and Zungaro jahu (jaú) are common in both ecoregions. Population genetics studies of some of these species above and below the Itaipu Dam suggest they are not isolated populations (Bignoto et al, 2009). These findings suggest that in years of very high discharge, individuals of large migratory species were able to cross the barrier of the Sete Quedas Falls in both directions.…”
Section: Final Consideration and Implications For Biodiversity Consermentioning
confidence: 91%
“…Due to its ease of use, low cost and high sensitivity, ISSR markers have been employed in studies on genetic diversity of several species of plants and animals (Luque et al, 2002;Bornet & Branchard, 2004;Askari et al, 2011;Moresco et al, 2013), as well as studies of sexual differentiation in plants (Ehsanpour et al, 2008) and identification of hybrid fish (Bignotto et al, 2009;AlmeidaFerreira et al, 2011). This marker has allowed the analysis of the main parameters used for determining the genetic diversity and the level of differentiation between species and natural populations of Neotropical fish (amount of polymorphic loci, expected or average heterozygosity and the number of migrants per generation) (Paiva et al, 2006;Sofia et al, 2006;Lopes et al, 2008;Antunes et al, 2010;Almeida-Ferreira et al, 2011;Domingos et al, 2014).…”
mentioning
confidence: 99%
“…For species with high economic value in aquaculture, ISSR has been used alone or in conjunction with mtDNA, to access intra-and interspecific phylogenetic relationships, and variation between stocks or their genetic structure (Bignotto et al, 2009;Xiaoxiao et al, 2011). In the present study, the 10 ISSR primers selected showed optimal efficiency, producing polymorphic patterns above 88.2% for the three broodstocks studied.…”
Section: Issr Markersmentioning
confidence: 72%